(untitled) (Journal of the College of Basic Education, 2022)
One of the concepts that the Noble Qur’an attached great importance to until it was considered a basic principle on which the legal laws are based is the concept of freedom, as the texts came to reinforce the rights of the children of Adam, regardless of their tongues and colors, in religious intellectual freedom, freedom of expression, freedom of marriage and divorce, freedom of work and travel. Study and other freedoms that fall within the rule (no harm, no harm). Since the term (freedom) was not mentioned in the Qur’an by its wording, but rather by its concept, we decided to follow the verses that define the Qur’anic concept of freedom and analyze its structural imperative to reach its argumentative function in order to stand on the limits of agreement or disagreement and to draw the frameworks of support or conflict with the concepts of freedom which the man-made laws came with.